Standard Correction of Vision Worsens EMG Activity of Pericranial Muscles in Chronic TMD Subjects - Annalisa Monaco; Eleonora Ortu; Mario Giannoni; Pierdomenico D’Andrea; Ruggero Cattaneo; Alessandra Mummolo; Davide Pietropaoli (Pain Research and Management)
Recent studies showed an evident correlation between the stomatognathic system and the visual system. These results suggest that subjects who are affected by both temporomandibular (TMD) disorders and refractive disorders present with altered control of pericranial musculature tone and higher open-eye electromyographic (EMG) values. The objective of this work was to evaluate the effects of standard vision correction on EMG in subjects suffering from TMD compared with application of the same vision treatments to non-TMD subjects. 40 subjects were enrolled in this study. The test group included 20 myopic subjects and also included patients with TMD. The control group included 20 healthy myopic subjects. All of the participants underwent a complete ocular examination and a sEMG analysis. The results showed that TMD subjects with vision disorders that are corrected with standard glasses present EMG values that are significantly higher than those presented by non-TMD subjects with vision disorders and standard glasses. Infact, in TMD subjects, eye correction did not have a positive effect on the stomatognathic or pericranial musculature.